Awareness and utilization of electronic databases collection by post-graduates students at Kenneth Dike Library, University of Ibadan: a case study (2014)
This study utilizes user’s study as a method for evaluating electronics databases collections at an institution with growing graduate research demands. The study focus group is the graduate students of the University of Ibadan with regards to their awareness, usability, and their feels about various issues surrounding the university electronic databases collections. The study employed descriptive survey research design using questionnaire to gather information from postgraduate students. Data was randomly collected from selected 200 post graduate students who visited the reference units of the main library and faculty libraries. Out of the 200 copies of questionnaire administered, 164 copies were returned representing 82% return rate. Findings indicate that the study group is aware of electronics databases in the library. It confirmed that 55.5 percent of PG students make use of the electronic databases daily for their research. AGORA and HINARI were the two mostly consulted by the respondents and lack of information literacy skills is an obstacle to the effective use of electronic database among post graduate students. Based on the findings of the study, it is recommended that creation of awareness among users about different electronics resources should be a priority for the university library management. Information retrieval skills training should be organized, at intervals, for users.